Comparative Analysis of Actual Cost and Indonesian Case-Based Groups Rate in Inpatient Suspect of Acute Hepatitis of Unknown Aetiology - Maemun, Siti; Widiantari, Aninda Dinar; Aliza, Nur; Setiawaty, Vivi; Rahmartani, Lhuri Dwianti (Malaysian Journal of Medical Sciences, 2026)
Background: Hospitals are crucial in implementing the referral and National Health Insurance (NHI) systems. The reimbursement structure by the Social Security Administrator for Health (SSAH) relies on the Indonesian Case-Based Groups (INA-CBG) method. This study aims to discern the variance between hospital inpatient costs and the corresponding inpatient INA-CBG rates, specifically for patients with suspected acute hepatitis of unknown aetiology (AHUA). Methods: This research used a descriptive cross-sectional method. We compared the actual hospitalisation cost and INA-CBG’s tariff in an Indonesian tertiary hospital from July to December 2022. The study encompasses patients with AHUA and uses a saturation sampling method. Results: Of the 17 patients suspected of AHUA, 16 made payments through NHI. A comprehensive analysis reveals that the total hospital costs based on INA-CBG rates show a deficit of IDR 21,604,464, reflecting a difference of 13.96%. The primary diagnoses among patients vary, with presentations of a combination of viral, bacterial, and parasitic infections alongside bile or liver disorders. The hospital incurred losses from services rendered to 10 patients. Notably, the significant allocations of hospital costs include laboratory (46.84%), pharmacy (19.01%), and accommodation (17.28%). Conclusion: To maintain effective cost control in inpatient services, the focus should prioritise medical appropriateness, explicitly referencing Clinical Practice Guidelines (CPG) and Clinical Pathways.